ChemInform Abstract: A Simple Diamine as Ligand in Iron‐Catalyzed Regioselective Allylic Alkylation. Issue 11 (8th March 2013) - Yu, Chenguang; Zhou, Aihua; He, Jing
Abstract TMEDA is found to be an efficient ligand in the process.